2014
DOI: 10.1037/a0032547
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal associations between depressive problems, academic performance, and social functioning in adolescent boys and girls.

Abstract: Depressive problems and academic performance, social well-being, and social problems in adolescents are strongly associated. However, longitudinal and bidirectional relations between the two remain unclear, as well as the role of gender. Consequently, this study focuses on the relation between depressive problems and three types of functioning in adolescents while testing gender differences. Depressive problems and functioning of 2,230 children were measured with structured questionnaires. The measurements too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
171
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(187 citation statements)
references
References 54 publications
15
171
0
1
Order By: Relevance
“…confidence and general well being at school (Verboom, Sijtsema, Verhulst, Penninx, & Ormel, 2014). Students' GPA was positively associated with development goals and to a lesser extent with demonstration-avoidance goals.…”
Section: The Role Of Individual Background Variablesmentioning
confidence: 84%
“…confidence and general well being at school (Verboom, Sijtsema, Verhulst, Penninx, & Ormel, 2014). Students' GPA was positively associated with development goals and to a lesser extent with demonstration-avoidance goals.…”
Section: The Role Of Individual Background Variablesmentioning
confidence: 84%
“…Adolescents with poor academic achievement are at risk of dropping out of school, which may place them in a situation of social risk [1,44]. A lack of basic education can harm adolescents and is associated with performing low-skilled, undemanding jobs, which provide little personal satisfaction.…”
Section: Perceived Academic Achievementmentioning
confidence: 99%
“…Second, sexist attitudes are related with different kinds of violence [10][11][12] Third, aggression is a vulnerability factor, which has been negatively associated with academic achievement [13]. Four, poor academic achievement is a social risk factor [1].…”
Section: Aims and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…Verboom, Sijtsema, Verhulst, Penninx, & Ormel, (2014) found that biological sex plays a role in the causal relationship between depression and subsequent achievement. These authors found only for girls but not for boys a statistically significant relationship.…”
Section: Chapter IV Discussionmentioning
confidence: 99%